Impact of Patient and Caregiver Transfer Training Provided by a Physical Therapist in the Hospice Setting: A Case Study. (March 2013) - Turner, Fernette; Seiger, Cindy; Devine, Nancy
Background: As patients in hospice become increasingly dependent upon caregivers, physical therapy interventions can minimize the risk of injury to the patient or caregiver that may occur during transfers between surfaces. Case Description: A 68-year-old male hospice patient was referred to physical therapy for strengthening and transfer training after a fall that resulted in the patient remaining in bed for 5 weeks due to an increased fear of falling. Treatments focused on caregiver training for correct transfer techniques. Outcome: During 10 treatment sessions, the patient and caregiver became independent and safe with all transfers. Although the patient's health declined, his risk for and fear of falling decreased. Confidence with transfers improved for the patient and caregiver. Discussion: Physical therapy "benefits were immeasurable" for the patient and caregiver by teaching them how to safely perform patient transfers with reduced risk of injury.